2016
DOI: 10.1177/1356766716649228
|View full text |Cite
|
Sign up to set email alerts
|

Building a place brand from the bottom up

Abstract: In an increasingly competitive global marketplace, the need for towns and cities to create a unique identity, to differentiate themselves from competitors, has become critical. Many places promote spectacular scenery, good quality of life, friendly people, and a sound business infrastructure. However, these factors are no longer differentiators, so places need a strong brand identity to stand out in order to attract people to live, work, and play. But brand development is often driven by short-term topdown app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 57 publications
0
11
0
1
Order By: Relevance
“…In practice, establishing a place branding strategy is often driven top-down by public administrators and materialized in a narrow-scope set of communication tactics to appeal to external, resourceful stakeholders [37]. City branding only seldom deploys the involvement of local citizens and stakeholders [29].…”
Section: The Concept Of City Brandingmentioning
confidence: 99%
“…In practice, establishing a place branding strategy is often driven top-down by public administrators and materialized in a narrow-scope set of communication tactics to appeal to external, resourceful stakeholders [37]. City branding only seldom deploys the involvement of local citizens and stakeholders [29].…”
Section: The Concept Of City Brandingmentioning
confidence: 99%
“…On one side, the selection of brand elements composing the brand identity is the core of the process [43], managed by key stakeholders in charge (e.g., destination management organization (DMO) and local authorities) which may adopt a more or less intense participative approach in the path of elements selections and elicitation [43][44][45]. Often through the design of a visual identity [41] and a communication plan, a brand promise is delivered into the market, as a defined and consistent message, in an attempt to impact the brand image [46][47][48]. On the other side, the process is intended as a cultural and social process steering interactions with many different stakeholders cocreating meanings [30], with the 'image in use' becoming a brand.…”
Section: City Brand Formationmentioning
confidence: 99%
“…Despite the importance of residents in developing, communicating, and legitimizing the place (destination) brand, the multifaceted roles of residents in the destination branding process has been overlooked (Kavaratzis and Hatch, 2013; Stylidis et al, 2016), whereas visitors’ perceptions of the destination have received prioritized attention (Hudson et al, 2016). Research has shown that failing to involve residents in the branding process sometimes leads to conflicts as differences in brand images and/or identity amongst various stakeholders create tension and, in some cases, disengagement from the created brand identity (Zenker and Petersen, 2014).…”
Section: Participatory Destination Brandingmentioning
confidence: 99%